2014
DOI: 10.1002/ana.24323
|View full text |Cite
|
Sign up to set email alerts
|

Salience network and parahippocampal dopamine dysfunction in memory‐impaired Parkinson disease

Abstract: Dopaminergic differences in the salience network and the medial temporal lobe contribute to memory impairment in PD. Furthermore, these findings indicate the vulnerability of the salience network in PD and its potential role in memory and executive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 70 publications
2
99
0
1
Order By: Relevance
“…Although the decline of ALFFs was more significant in the R-putamen, the selective lateral effect must be regarded cautiously due to the small sample size. However, previous studies did report neural disruptions can be more pronounced on the right side in AD-associated neurodegeneration [35, 36]. Further study is needed to clarify laterality issues.…”
Section: Discussionmentioning
confidence: 86%
“…Although the decline of ALFFs was more significant in the R-putamen, the selective lateral effect must be regarded cautiously due to the small sample size. However, previous studies did report neural disruptions can be more pronounced on the right side in AD-associated neurodegeneration [35, 36]. Further study is needed to clarify laterality issues.…”
Section: Discussionmentioning
confidence: 86%
“…Graph theoretical analyses have revealed a decreased hub role in the left dorsal anterior insula in PD patients compared to healthy controls (HCs) (Tinaz et al, 2016). Furthermore, recent data from our group have demonstrated that D2 receptor availability in the anterior insula was associated with executive and memory dysfunction in PD patients with mild cognitive impairment (Christopher et al, 2014b, 2015). Thus, the anterior insula, in particular, seems to be a critical “hub” for cognitive impairment in Parkinsonian patients (Christopher et al, 2014a; Criaud et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…Specifically, the DRD2 system is linked to transient memory updating processes 31, 32. A reduction in D2 receptors has been found in PD13 and in imaging studies, memory deficits in PD are correlated with reduced extrastriatal D2 receptor binding in the medial temporal lobe, including the insula, in parts of the so‐called salience network 14. The present findings of poorer performances in attention and episodic memory and an increased risk of dementia in DRD2 957 T/T carriers with PD could, potentially, relate to reduced function or increased vulnerability in D2‐dependent “salience networks” of the brain (eg, in medial, temporal structures).…”
Section: Discussionmentioning
confidence: 99%
“…The 957 C/C genotype correlates with higher D2 receptor densities in extrastriatal, thalamic and neocortical areas,11 and better episodic memory in healthy elders 12. Hypofunction of extrastriatal dopamine receptor D2 subsystems, including in the insula, was recently found to contribute to cognitive decline in PD 13, 14…”
Section: Introductionmentioning
confidence: 99%